2022
DOI: 10.3390/app12126128
|View full text |Cite
|
Sign up to set email alerts
|

Methane Production Potential from Apple Pomace, Cabbage Leaves, Pumpkin Residue and Walnut Husks

Abstract: Circular economy aims to eliminate organic waste through its transformation, composting and processing into other products or energy. The main aim of the study was to determine the specific methane yield (SMY) of anaerobic digestion (AD) of four different fruit and vegetable residues (FVR). In addition, the reduction in greenhouse gas (GHG) emissions was calculated based on the assumption that maize will be replaced by the FVR as a feedstock for biogas production. The SMY of four residues (apple pomace, cabbag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…A similar relationship can be observed for other biofuels obtained from agricultural raw materials [46]. In biogas production, one can strive to reduce the cost of the raw material and increase the efficiency of biogas from the raw material by using organic waste where available [47,48]. However, it is only profitable on the local scale, where there is no competition over the raw material and with low logistic costs [49,50].…”
Section: Factors Determining the Profitability Of Biogas Plantssupporting
confidence: 55%
“…A similar relationship can be observed for other biofuels obtained from agricultural raw materials [46]. In biogas production, one can strive to reduce the cost of the raw material and increase the efficiency of biogas from the raw material by using organic waste where available [47,48]. However, it is only profitable on the local scale, where there is no competition over the raw material and with low logistic costs [49,50].…”
Section: Factors Determining the Profitability Of Biogas Plantssupporting
confidence: 55%
“…Yan et al [27] reported cauliflower residues generated a methane yield of 249.61 mL/gVS. Czubaszek et al [28] found the highest methane yield of 297.81±0.65 L/kgVS during the anaerobic digestion of cabbage leaves. Compared to the previous literature, the theoretical methane yield obtained in this study is almost close to the experimental methane yield obtained by the anaerobic digestion of mustard residuals, with a yield difference of 4.27%.…”
Section: Correlation Between Cod Total Dilution Volume and Theoretica...mentioning
confidence: 99%
“…One of the directions that makes it possible to increase the return on investment and operation of AD plants is the utilisation of organic waste [10]. Heavily polluted wastewater from the food industry [11], sewage sludge [12,13], waste from agriculture [14], the fruit and vegetable sector [15] and the meat industry [16], as well as the organic fraction of municipal waste [17] and many others [18][19][20][21] are excellent substrates in this process. Another way to increase economic efficiency is to use technologies and process units that increase the biodegradability of the substrates used, which has a positive effect on the quantity and qualitative composition of the biogas produced [22].…”
Section: Introductionmentioning
confidence: 99%